2018
DOI: 10.1093/mnras/sty3500
|View full text |Cite
|
Sign up to set email alerts
|

The neutral hydrogen properties of galaxies in gas-rich groups

Abstract: We present an analysis of the integrated neutral hydrogen (H i) properties for 27 galaxies within nine low mass, gas-rich, late-type dominated groups which we denote "Choirs". We find that majority of the central Choir galaxies have average H i content: they have a normal gas-mass fraction with respect to isolated galaxies of the same stellar mass. In contrast, we find more satellite galaxies with a lower gas-mass fraction than isolated galaxies of the same stellar mass. A likely reason for the lower gas conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 113 publications
(224 reference statements)
5
39
0
Order By: Relevance
“…In Džudžar et al (2019a) we analysed the integrated H i properties of 27 galaxies within nine Choir groups and compared them to a sample of isolated galaxies. We explored the H i mass fraction, specific star formation rate, star formation efficiency, H i deficiency, H i mass-size relation and stability parameter of the group galaxies with respect to the isolated galaxies.…”
Section: From Singg To Choirsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Džudžar et al (2019a) we analysed the integrated H i properties of 27 galaxies within nine Choir groups and compared them to a sample of isolated galaxies. We explored the H i mass fraction, specific star formation rate, star formation efficiency, H i deficiency, H i mass-size relation and stability parameter of the group galaxies with respect to the isolated galaxies.…”
Section: From Singg To Choirsmentioning
confidence: 99%
“…Presented H i maps and spectra use velocities in the optical convention. The group distances are based on the multipole attractor model (Mould et al 2000), as in (Meurer et al 2006;Sweet et al 2013 andDžudžar et al 2019a).…”
Section: From Singg To Choirsmentioning
confidence: 99%
“…Obreschkow et al (2016) proposed a hybrid stability model that predicts the mass fraction of atomic (hydrogen+helium) gas as a function of mass and specific angular momentum of the whole (gas+stars) disc, assuming a constant H i velocity dispersion: fHI = min{1, 2.5 q 1.12 }, where q = j disc σHI/GM disc and σHI = 10 km s −1 . Such a ⋆ E-mail: romeo@chalmers.se stability model has been tested in a variety of applications (e.g., Lagos et al 2017;Lutz et al 2017Lutz et al , 2018Stevens et al 2018;Wang et al 2018;Džudžar et al 2019;Murugeshan et al 2019;Stevens et al 2019). Another important contribution is the one by Zasov & Zaitseva (2017), who showed that the relation between atomic gas mass and disc specific angular momentum is equally well described by a simpler stability model controlled by Qgas, the gas Toomre parameter, assuming that Qgas is approximately constant within a galaxy (like σgas).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the H i modeling and the Ks-band (background subtracted) galaxy image, we derive the total baryonic specific angular momentum (j) and stability parameter (q) of the galaxy utilizing the robust method described in Murugeshan et al (2019). We determine that the global stability parameter (q) is in overall agreement with the one determined analytically by Džudžar et al (2019). Obreschkow et al (2016) observe a tight positive correlation between the atomic gas-mass fraction and the global stability parameter q (with its ability to regulate star formation efficiency) which consequently determines the atomic gas fraction.…”
Section: Modeling Of Eso156-g029mentioning
confidence: 92%
“…The integrated properties of ESO156-G029 were shown in Džudžar et al (2019) -galaxy with ID: HIPASSJ0400-52:S1. We found that ESO156-G029 is an H i-rich galaxy with a large gas-mass fraction and a low specific star formation efficiency.…”
Section: Eso156-g029mentioning
confidence: 99%